THE ROLE OF RELIGIOUS GUIDANCE IN INCREASING THE LIFE SATISFACTION OF ELDERLY - Noval Gerian; Iin Indriyani; Kurnia Sintia; Basyar, M; Cheazar, H; Masayu, H; Menti Susanti; Purwaningsih; Nova Risky; Muhammad Fawwaz; Rossa Lara; Nyimas Salsabila; Maula Habib (CV. Doki Course and Training, 2023)
This research was conducted at Lanjut Usia Harapan Kita Social Institutional Care to detect the level of life satisfaction of the elderly through the role of religion, especially the elderly who are in institutional care. This study uses a qualitative approach with the phenomenological approach as the purpose of this study is to portray the circumstance that occurs. Researchers utilize a non-random sampling technique to obtain research respondents. Purposeful Sampling is one of the techniques of non-random sampling techniques (Creswell: 2012). There exists a way to do purposeful sampling according to Creswell, namely “Typical Case Sampling”. For data mining techniques, we utilize the triangulation method, it is utilized to depict the phenomena that exist in the research area, there exist interview, observation, and documentation. We determine at least four people in institutional care who will be appropriate subjects in our research and they are disposed to undertake a live interview. We discover that both of those four subjects realize that religion is crucial in increasing their life satisfaction, at least convincing them to pass demise serenely.